2016
DOI: 10.1557/mrc.2016.10
|View full text |Cite
|
Sign up to set email alerts
|

Local-structure-affected behavior during self-driven grain boundary migration

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Specifically, GB-mediated deformation mechanisms, such as GB sliding [9,10], GB migration [11], or grain rotation [12], are prevalent and at least partly linked with GB annihilation in metallic nanocrystalline materials [13]. A variety of studies have been focused on the mechanical response of individual GBs [14,15], however, the nanocrystalline networks, consisting of multiple GBs, may exhibit different kinetic behaviors [16,17], which was rarely studied. The plastic deformation behavior in polycrystals, involving cooperative motion and interactions of parallel GBs or GB junctions [18,19], plays an important role and must be taken into account in practice.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, GB-mediated deformation mechanisms, such as GB sliding [9,10], GB migration [11], or grain rotation [12], are prevalent and at least partly linked with GB annihilation in metallic nanocrystalline materials [13]. A variety of studies have been focused on the mechanical response of individual GBs [14,15], however, the nanocrystalline networks, consisting of multiple GBs, may exhibit different kinetic behaviors [16,17], which was rarely studied. The plastic deformation behavior in polycrystals, involving cooperative motion and interactions of parallel GBs or GB junctions [18,19], plays an important role and must be taken into account in practice.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, by using in situ HRTEM, Luo et al have reported the adjustment of GB structures of Cu film during a self-driven GB migration, which involves GB dissociation, partial dislocation emission from GB, and faceting/defaceting [61]. Furthermore, they revealed that GB migration ability is closely related to the local GB segment consisting of "hybrid" structural units.…”
Section: Study Of Grain Boundary Charactermentioning
confidence: 99%
“…[44] GB migration would also be involved in grain growth to combine the small neighbor grains. During the migration process, the local GB environment would be changed, [50][51][52] which would promote the emission of the partial along with local changes in GB orientation, GB structure and GB dislocation distribution. [50,53,54] Furthermore, coupled with the high stress concentration at the crack tip, numerous twinning partials would be emitted from the GBs to form a twin.…”
Section: Twinning Mechanismsmentioning
confidence: 99%
“…During the migration process, the local GB environment would be changed, [50][51][52] which would promote the emission of the partial along with local changes in GB orientation, GB structure and GB dislocation distribution. [50,53,54] Furthermore, coupled with the high stress concentration at the crack tip, numerous twinning partials would be emitted from the GBs to form a twin. Thus, successive emission of partials would happen during the grain growth process, so that we can observe the highly curved TB with so many TBs connected by ITBs, as shown in Figure 2(c).…”
Section: Twinning Mechanismsmentioning
confidence: 99%